DETERMINING LEVEL OF NURSING STUDENTS DIAGNOSING THE SYMPTOMS AND RISKS OF CHILD ABUSE AND NEGLECT - DEMİR ACAR, Mukaddes and BULUT, Elif (Göbeklitepe Medical Science Journal, 2021)
Objectives: This study is to review the nursing students’ levels of diagnosing the symptoms and risks of child abuse and neglect. Methods: The sample of the study consisted of 181 students studying in the 3rd and 4th grades in the Nursing Department of the Faculty of Health Sciences of a university in Turkey. Institutional and ethical committee permission was obtained for the study. The data were collected in January-February 2020 using the Introductory Information Form and the Scale Form for Diagnosing the Symptoms and Risks of Child Abuse and Neglect. Statistical analyzes were performed in SPSS 24.0 package program. Results: 81.8% of the students participating in the study are girls, the average age is 21.15 ± 1.87, 50.8% are in the 4th grade, and 14.4% were the only child in their family. It was determined that the total mean score of the students for the diagnosis of the signs and risks of child abuse and neglect was 3.71 ± 0.56, 79% wanted to receive training on this subject, and 86.7% observed children in terms of abuse and neglect in the unit where they practiced. The mean score for diagnosing the signs and risks of child abuse and neglect among students without siblings was lower than the mean score of students with more than one sibling, and the statistical difference between the groups was found to be significant. The difference between the groups was not statistically significant according to the students’ total score averages and their class, gender, perception of economic situation, place of residence, family type, perception of knowing the characteristics of the child and family exposed to child neglect and abuse, and observing children in terms of neglect and abuse in the unit where the application was made. Conclusions: The study showed that the average scores of nursing students for diagnosing signs and risks of child abuse and neglect are similar to the literature and should be improved